2016
DOI: 10.3982/qe399
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference in a class of partially identified models

Abstract: This paper develops a Bayesian approach to inference in a class of partially identified econometric models. Models in this class are characterized by a known mapping between a point identified reduced-form parameter μ and the identified set for a partially identified parameter θ. The approach maps posterior inference about μ to various posterior inference statements concerning the identified set for θ, without the specification of a prior for θ. Many posterior inference statements are considered, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
134
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(144 citation statements)
references
References 55 publications
10
134
0
Order By: Relevance
“…In addition we have direct beliefs about the lagged structural coefficients as captured by the terms r i and V i in equations (34) and (35). This added information is used only for i = 3, the monetary policy rule, where the expectation is that the third element of b 3 should be close to ρ.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition we have direct beliefs about the lagged structural coefficients as captured by the terms r i and V i in equations (34) and (35). This added information is used only for i = 3, the monetary policy rule, where the expectation is that the third element of b 3 should be close to ρ.…”
mentioning
confidence: 99%
“…5 Moon et al (forthcoming) and Gafarov et al (2018) developed algorithms to estimate the identified set or its bounds using a frequentist approach, while Kline and Tamer (2016) discussed Bayesian posterior inference about the identified set in a general context. Giacomini and Kitagawa (2015) and Gafarov et al (2016) noted that the identified set could be interpreted and calculated as robust Bayesian posterior inference across the set of all possible Bayesian prior distributions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…See the 2009 NBER working paper version of Moon and Schorfheide (2012), Kitagawa (2012), Kline and Tamer (2015), Liao and Simoni (2015) and the references therein. 7,8 Theoretically, all these papers consider separable models and use various renderings of a similar intuition.…”
Section: Several Papers Have Recently Proposed Bayesian (Or Pseudo Bamentioning
confidence: 99%
“…Other related papers that explicitly consider inference on projections include Andrews, Berry, and Jia (2004), Beresteanu and Molinari (2008), Bontemps, Magnac, and Maurin (2012), Chen, Tamer, andTorgovitsky (2011), Kaido (2012), Kitagawa (2012), Kline and Tamer (2015) and Wan (2013). However, some are Bayesian, as opposed to our frequentist approach, and none of them establish uniform validity of confidence sets.…”
Section: Introductionmentioning
confidence: 99%